The relation of sex, occupational status and age on the different barriers limiting access to dental care - Briones, Sherrie Ann V.
This study was conducted in order to determine the barriers which limit access of the residents of Villa Penafrancia Subdivision, Batangas City to dental care. It was done to describe the barriers which limit the dental care delivery system to the different subgroups of patient namely: sex, occupational status and age. In the study, out of 90 questionnaires that were distributed to the residents of Villa Penafrancia Subdivision, Batangas City, 72 were returned and tallied to know the major factors that serve as barriers to accessing dental care. The subjects were divided into different subgroups based on age, sex and occupational status in order to find its relationship to the different barriers that limit access to dental care. The questionnaire contained 41 statements pertaining to the presence or absence of dental professional factors. These factors include lack of access, financial constraint, miscommunication, unprofessionalism of dentists, incompetent auxiliary personnel, deficient equipment, mismatch between the patient and the dentist perception of needs, defective work and poor clinical condition. The mean, percentage and rank were computed. Chi-square test was also used to describe the different barriers among the different subgroups of patients. Results showed that there was no significant difference for each subgroup. This means that their citation of responses is independent of their grouping or has no statistically significant relation to their grouping. However, the most common factor that serves as barrier as perceived by the patients is financial constraint.